Manyampir: Pengobatan Alternatif Masyarakat Bakumpai di Kelurahan Lepasan Kabupaten Barito Kuala - Kharisma, Muhammad; Effendi, Rusdi; Akmal, Helmi (Lambung Mangkurat University, 2022)
Communities in several regions in Indonesia have used a wide variety of traditional medicines. People in one area have traditional medicines that are different from people in other areas, and this is due to the biodiversity that exists in the environment where they live. Their local wisdom triggers the emergence of various cultural products. This study aims to describe the meaning and function of Manyampir, how to structure Manyampir, and how to use the Manyampir ritual as a traditional alternative medicine. Historical research methods conducted this research. The first stage in this research is to collect resources through literature study and field studies. After collecting the data, enter the source criticism stage to see the authentic source. Then the next stage is interpretation, which is analyzing the data that has been criticized. Finally, the historiography stage presents data in written form. The results of the study note that the Bakumpai community in Lepasan Village, Bakumpai District, Barito Kuala Regency, conducted traditional alternative medicine Manyampir as one alternative treatment solution and interpreted as a multifunctional card.